"Back to the future?" Cuban–Russian relations under Raúl Castro. Issue 2 (June 2015) - Bain, Mervyn J.
Abstract: Since Raúl Castro has become the President of Cuba relations between Moscow and Havana have displayed a number of reminiscence of the halcyon days of Soviet–Cuban relations, which has included Raúl Castro and Dmitry Medvedev traveling to Russia and Cuba twice, respectively and Vladimir Putin visiting the Cuban capital in July 2014. Correspondingly, this article will examine the relationship that is developing between the two countries with the aim to find out whether the bilateral relationship has "gone back to the future" since August 2006. Also it should conclude if a "Raúl" doctrine' similar to the "Putin doctrine, " which has been vital for this relationship, has emerged within the realm of Cuban foreign policy.